The collapse of constitutional remedies - Huq, Aziz Z. (New York, NY : Oxford University Press, 2021)
Aziz Z. Huq examines what happens when our constitutional rights are violated. Many people think that federal courts will step in then and provide a remedy. But for most people, and especially for the vulnerable in our society, they won't lift a finger. As Huq argues, the powerful often get quicker access to the courts and more fulsome judicial review, which shows a break from the way in which the courts were originally designed. This book shows the deep ironies of judicial independence and charts a part of getting free of its most baleful effects.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on April 8, 2022).
Keywords: Constitutional torts -- United States; Government liability -- United States; Remedies (Law) -- United States; Judicial independence -- United States; Political questions and judicial power -- United States